2002
DOI: 10.1046/j.1524-4741.2002.08407.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Estrogen Receptor Polymorphism in Codon 325 by PCR-SSCP in Breast Cancer: Association With Lymph Node Metastasis

Abstract: Breast cancer is the most frequent neoplasm in women. Expression of the estrogen receptor (ER) has a key role in breast cancer; the ER gene is located at chromosome 6q24-q27 and is made up of 8 exons with a total of 140 kb. The polymorphism in codon 325 of exon 4 (ER325) is a transition CCC-->CCG. The objective of this study is to analyze the frequency of this polymorphism in breast cancer using the polymerase chain reaction single-strand conformation polymorphism (PCR-SSCP) technology. DNA was extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…In the literature, this SNP was investigated especially in relationship with breast cancer but the results were not convergent: some studies found the G allele protective [47] while other studies found increased risk with G allele [49][50][51] and another found no risk [52,53] or found a risk only when included this polymorphisms in haplotypes [41,54,55]. In our study, we found the minor allele G protective for the total number of cancer cases.…”
Section: Discussioncontrasting
confidence: 74%
“…In the literature, this SNP was investigated especially in relationship with breast cancer but the results were not convergent: some studies found the G allele protective [47] while other studies found increased risk with G allele [49][50][51] and another found no risk [52,53] or found a risk only when included this polymorphisms in haplotypes [41,54,55]. In our study, we found the minor allele G protective for the total number of cancer cases.…”
Section: Discussioncontrasting
confidence: 74%
“…According to FASTSNP prediction report, the C allele of rs1801132 disrupts also the binding site for GATA-1 and GATA-2 transcription factor. In the literature, the results were divergent: some studies found the G allele protective [38] while other studies found increased risk with G allele [40][41][42]; other studies found no risk [43][44] or found risk only when included this polymorphisms in haplotypes [33,[45][46]. In our study, rs1801132 showed a trend to be associated with the age at diagnosis (genotype 11 associated with onset of cancer after 50 years, p=0.024), hypercholesterolemia (p=0.003) and increased BMI (p=0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Vasconcelos et al [21] suggested that there was a relationship between the ESR1 P325P polymorphism and breast cancer risk (cases = 70 and controls = 69; OR, 2.3; 95% CI, 1.1- [3,15]. Akisik et al [22] observed no significant difference between patients and control groups for the ESR1 T594T (cases = 149 and controls = 153; OR, 1.6; 95% CI, 0.3-9.4).…”
Section: Discussionmentioning
confidence: 99%